Investigation in blood-brain barrier integrity and susceptibility to immune cell penetration in a mouse model of Dravet syndrome - Cristina Alonso; Alicia García-Culebras; Valentina Satta; Inés Hernández-Fisac; Álvaro Sierra; José A. Guimaré; Ignacio Lizasoain; Javier Fernández-Ruiz; Onintza Sagredo (Brain, Behavior, & Immunity - Health)
Dravet Syndrome (DS) is a pediatric encephalopathy caused by mutations in Scn1a gene encoding the α1 subunit of the NaV1.1 voltage-gated sodium channel, which lead to early febrile seizures that progress to severe tonic-clonic seizures and several long-term behavioural comorbidities. In the present study, we have investigated whether a possible early deterioration in the blood-brain barrier (BBB) may facilitate the infiltration of immune cells to the brain parenchyma, which may contribute to these pathogenic events. In this study, conditional knock-in Scn1a-A1783V mice and their controls were used at the postnatal day (PND25): (i) to compare their levels of several immune cell populations in the bone marrow and blood; and (ii) to analyze several BBB proteins, as well as the occurrence of immune cell infiltration and endogenous immunoglobulin G (IgG) extravasation into the brain parenchyma. Our data revealed an elevation in the number of neutrophils in the blood of DS mice, but not of B- and T-cells, despite the levels of these immune cells were significantly reduced in the bone marrow. The elevated number of blood neutrophils did not apparently originate their infiltration into the hippocampus of DS mice as an immunofluorescence analysis indicated, and the same happened in B- and T-cells. However, the levels of endogenous IgG in this brain structure were significantly elevated in DS mice compared to controls, directly indicating the occurrence of extravasation into the brain parenchyma and indirectly that the BBB in DS mice may be relatively affected, a fact confirmed by the reduction in the levels of BBB-related proteins such as ZO-1 in these mice. In conclusion, our results support the occurrence of certain degree of deterioration in the BBB in DS, which may facilitate the infiltration of immune cells to the brain, then contributing to the pathogenesis in this disease.